42 : Inside the Presidency of Bill Clinton - Riley, Russell L. (Russell Lynn), 1958-; Perry, Barbara A. (Barbara Ann), 1956-; Nelson, Michael, 1949- (Book collections on Project MUSE., 2016)
This book uses hundreds of hours of newly opened interviews and other sources to illuminate the life and times of the nation's forty-second president, Bill Clinton. Combining the authoritative perspective of these inside accounts with the analytic powers of some of America's most distinguished presidential scholars, the essays assembled here offer a major advance in our collective understanding of the Clinton White House. Included are path-breaking chapters on the major domestic and foreign policy initiatives of the Clinton years, as well as objective discussions of political success and failure. p›42 is the first book to make extensive use of previously closed interviews collected for the Clinton Presidential History Project, conducted by the Presidential Oral History Program of the University of Virginia's Miller Center. These interviews, recorded by teams of scholars working under a veil of strict confidentiality, explored officials' memories of their service with President Clinton and their careers prior to joining the administration. Interviewees also offered political and leadership lessons they had gleaned as eyewitnesses to and shapers of history. Their spoken recollections provide invaluable detail about the inner history of the presidency in an age when personal diaries and discursive letters are seldom written. The authors producing this volume had first access to more than fifty of these cleared interviews, including sessions with White House chiefs of staff Mack McLarty and Leon Panetta, Secretaries of State Warren Christopher and Madeleine Albright, National Security Advisors Anthony Lake and Sandy Berger, and a host of political advisors who guided Clinton into the White House and helped keep him there. This book thus provides a multidimensional portrait of Bill Clinton's administration, drawing largely on the observations of those who knew it best.p›ContributorsSpencer D. Bakich, University of RichmondBrendan J. Doherty, United States Naval AcademyPatrick T. Hickey, West Virginia Universityp›Elaine Kamarck, Center for Effective Public Management, Brookings InstitutionSidney M. Milkis, University of VirginiaMegan Moeller, University of Texas at AustinMichael Nelson, Rhodes College and the Miller Center, University of Virginia›Bruce F. Nesmith, Coe CollegeBarbara A. Perry, Miller Center, University of VirginiaPaul J. Quirk, University of British Columbiap›Russell L. Riley, Miller Center, University of VirginiaAndrew Rudalevige, Bowdoin CollegeRobert A. Strong, Washington and Lee UniversitySean M. Theriault, University of Texas at Austin.